An in vivo study on the anticarcinogenic effect of dioscorea hispida dennst - Sapida, Sheila T.
This experimental study aimed to determine the effect of Dioscorea Hispida Dennst. on mice induced with oral cancer using 4-NQO. Thirty ICR male mice ages 4-5 weeks old were used as subjects in the study. They were divided into groups A, B, C, D, E and F. Group A was given rabbit pellets and water as their basal diet, they were not given 4-NQO nor Dioscorea Hispida. Groups B, D, E and F, were given 4-NQO as carcinogen and groups C, D, E and F were also given Dioscorea Hispida as anticarcinogen. After four weeks of inducing cancer and at the same time giving them the experimental drug with varying doses, they were subjected to biopsy and to histological examinations. Using descriptive analysis, it has been found that histological manifestations of oral cancer decreases as the dosage of Dioscorea Hispida increases.